Enhanced production of extracellular urate oxidase by Aspergillus Flavus - Wan Ruhayu, Wan Ramli (2013)
Urate oxidase or uricase is an enzyme that catalyses the oxidation of uric acid to allantoin and plays important rule in purine metabolism. The first important application discovered for uricase was in clinical biochemistry as diagnosis reagent for measurement of uric acid in blood. The precipitation of uric acid can leading to gout symptom. The main purpose of this research is to optimize the culture condition for maximum uricase production by Aspergillusfiavus. The parameters studied were pH (range of 4 to 8), the sucrose concentration (lOg/i to 50 Wi) and the agitation rate (100 to 300 rpm). The Aspergillus flavus were inoculated in yeast extract with sucrose and incubated for 24 hours at 200 rpm and 30°C. The maximum enzyme activity obtained from the experiment is 0.03974 U/ml at pH 6, 200 rpm and 30 g/l sucrose concentration. Since the optimum conditions were obtained, the production of uricase can be enhanced and world demand on uricase can be fulfill in the future.